Harmoni dan Kearifan Lokal di Era Majapahit Situs Sumur Upas dan Candi Kedaton - Ridlo, Miftakhur; Mahfudz, Lauhul; Muhammad, Ery Yanda (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
The Majapahit Kingdom was one of the largest Hindu-Buddhist empires in Southeast Asia, leaving behind numerous monumental legacies, including Kedaton Temple and the Sumur Upas Site in Trowulan, Mojokerto. These sites hold historical, archaeological, and spiritual significance, reflecting the acculturation between Hindu-Buddhist traditions and the emergence of Islam during the late Majapahit era. This study employs historiographical methods comprising heuristics, verification, interpretation, and historiography to explore the functions, meanings, and socio-religious dynamics surrounding the sites. Findings such as multilayered brick structures, foreign ceramics from China and Southeast Asia, ancient coins, and Islamic gravestones indicate that the area once served as a center of religious and social activity, marking the growing influence of Islam within Majapahit society. Local traditions, such as the Bari’an ritual and the use of sacred well water still preserved today demonstrate the embodiment of local wisdom in maintaining interfaith and intercultural harmony. This study highlights that the development of culture and Islam during the Majapahit period shared common values of harmony, forming an essential foundation for social cohesion and cultural pluralism in contemporary Indonesian society.